Periferna arterijska bolezen - Adamič, Petra (Medicinski razgledi, 2011)
The incidence of peripheral arterial disease is increasing due to the aging ofthe population. In the asymptomatic stage, atherosclerotic plaques are present but not clinically evident. However, their growth could narrow the vessel and become manifested as intermittent claudication. Further worsening of ischemia could lead to trophic changes of the skin and adnexa, ulceration and even gangrene. Therefore, early detection and prevention of disease progression is very important. This paper focuses on the main risk factors forperipheral arterial disease, as well as the relevant diagnostic procedures and treatment options in different stages of the disease. The main treatments of choise include supervised walking programs and systemic prevention of cardiovascular ischemic events. When conservative treatment is inefficient, the percutaneus revascularization method should be considered. For long vesselocclusions or highly calcified plaques, bypass grafting is us ed to reestablish normal blood flow. Amputation is the procedure of last resort, indicated for extensive, de ep necrosis and progressive gangrene. Despite modern preventive measures, the mortality of patients with peripheral arterialdisease is higher than in the general population. Due to the exceptionally elevated risk for cardiovascular events, the majority of these individuals will eventually die of cardiac or cerebrovascular problems.
Keywords: Intermitetna klavdikacija; Peripheral Vascular Diseases; Ishemija; Arterial Occlusive Diseases; Diagnosis; Periferne žile, bolezni; Therapy; Arterijske, okluzivne bolezni; Intermittent Claudication; Noga, ulkus; Ischemia; Gangrena; Leg Ulcer; Mikrocirkulacija; Microcirculation; periferan arterijska bolezen; Gangrene; dejavniki tveganja; diagnostika; zdravljenje